Reshaping Europe In A Multipolar World: Can The EU Rise To The Challenge? - Dean Carroll (Central European Journal of International & Security Studies, 2011)
Globalisation and the emergence of economic players such as Brazil, Russia, India and China (BRIC) have led to predictions that US hegemony will quickly decline as a new world order emerges. With the European Union (EU) also facing a downgrading of its own status – as economic, political and cultural power shifts from west to east – now is the time to ensure the Union has a strategy in place to remain an influential global actor despite its lack of natural resources and member state sovereign debt arising from the 2008/9 economic crisis. Only concerted efforts at institutional future-proofing (or widening and deepening plus) by the EU and a global vision for the supranational body will ensure its survival and prosperity.